Diversified abietane family diterpenoids from the leaves of Leucosceptrum canum and their cytotoxic activity. (January 2019) - Guo, Kai; Liu, Yan-Chun; Liu, Yan; Luo, Shi-Hong; Li, Wen-Yuan; Li, Xiao-Nian; Li, Sheng-Hong
Abstract: Twenty-four diterpenoids of abietane family, including thirteen undescribed compounds and eleven known ones, were isolated from the leaves of Leucosceptrum canum . Their structures were elucidated by comprehensive spectroscopic analyses (including 1D and 2D-NMR and HRMS), and in the case of 15-hydroxy-abieta-8, 11, 13-trien-3-one by single-crystal X-ray diffraction. Their frameworks are highly diversified, involving normal abietane, 9, 10-epoxy-9, 10- seco -abietane, 18(4 → 3)- abeo -abietane, 3, 4- seco -18(4 → 3)- abeo -abietane, and 16- nor -abietane. Selected compounds were evaluated for their cytotoxic activity against three human tumor cell lines, NCI-H1975, HepG2 and MCF-7. Among them, 3β-hydroxy-abieta-8, 13-diene, 3β-hydroxy-abieta-8, 11, 13, 15-tetraene, and 3β-hydroxy-9, 10-epoxy-9, 10- seco -abieta-8, 11, 13-triene exhibited moderate cytotoxicity against all three cell lines with IC50 values ranging from 8.11 to 50.73 μM, while 3α-hydroxy-abieta-8, 11, 13, 15-tetraene, 3β-hydroxy-abieta-8, 11, 13, 15-tetraen-7-one, and 15-hydroxy-18(4 → 3)- abeo -abieta-3, 8, 11, 13-tetraene were selectively active with IC50 values ranging from 28.80 to 71.29 μM. Graphical abstract: Thirteen undescribed abietane family diterpenoids along with eleven known ones were isolated from the aerial parts of Leucosceptrum canum . Six of them showed moderate cytotoxic activity.Image 1 Highlights: Twenty-four including 13 undescribed abietanoids were isolated from Leucosceptrum canum. Their skeletons included normal, seco-, abeo -, seco - abeo- and nor -abietanes. Six abietanoids showed moderate cytotoxicity against three tumor cell lines. This is the first report of abietane family diterpenoids from Leucosceptrum canum.